Obesity and the obesity paradox in abdominal aortic aneurysm - Lu, Feng; Lin, Yong; Zhou, Jianshun; Chen, Zhen; Liu, Yingying; Zhong, Maolin; Wang, Lifeng (Frontiers in Endocrinology, 2024)
Obesity, characterized by its complexity and heterogeneity, has emerged as a significant public health concern. Its association with increased incidence and mortality of cardiovascular diseases stems not only from its complications and comorbidities but also from the endocrine effects of adipose tissue. Abdominal aortic aneurysm (AAA), a chronic inflammatory condition, has been closely linked to obesity. Intriguingly, mild obesity appears to confer a protective effect against AAA mortality, whereas severe obesity and being underweight do not, giving rise to the concept of the "obesity paradox". This review aims to provide an overview of obesity and its paradoxical relationship with AAA, elucidate its underlying mechanisms, and discuss the importance of preoperative weight loss in severely obese patients with AAA.